Primary pulmonary hypertension and human immunodeficiency virus infection - Conly, J (Pulsus Group Inc, 1997)
This report details the case of a 42-year-old homosexual Caucasian male with infection due to human immunodeficiency virus type 1 (HIV-1) who presented with a four-month history of progressive dyspnea and was found to have clinical and hemodynamic evidence of severe pulmonary hypertension. He had had no opportunistic infections, and had a T helper lymphocyte count of 200×10(6)/L. Extensive clinical laboratory and radiological evaluations revealed no underlying cause. Microscopic examination of postmortem lung tissue revealed findings consistent with grade V pulmonary hypertension. Electron microscopic analysis and polyermase chain reaction detection of HIV-DNA from dissected pulmonary arterioles failed to provide any supportive evidence to suggest productive infection of the pulmonary arteriolar endothelial cells by HIV-1. Although HIV-1 likely plays a role in the pathogenesis of primary pulmonary hypertension, evidence for direct infection of pulmonary vessel endothelium was lacking in this case. The pathogenesis of primary pulmonary hypertension associated with HIV remains obscure.